Perancangan User Experience Mobile Learning menggunakan Metode Design Thinking (Studi Kasus : SD Negeri Wates Kabupaten Kediri) - Rr. Tasia Haniifah Rihadatul Aisy; Komang Candra Brata; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The COVID-19 pandemic has disabled face-to-face activities, including education. SDN Wates is one of the educational institutions whose learning process has changed to online. SDN Wates chose to use a messaging application as a means of learning and disseminating information. The absence of face-to-face meetings between teachers and students has an impact on the decline in student grades. Teachers also have difficulty in carrying out the learning process, making report cards, and obtaining school information. Starting from these problems, we need media that can support online learning. Using e-learning as a learning medium cannot be applied because only 30% of teachers and 9.7% of students have laptops. The purpose of this study is to propose a design solution that can solve the problems experienced and adapted to existing limitations. User experience design is needed to create a well-accepted interface and function. The method used is design thinking to find solutions to problems by considering needs, technology limitations, and business needs. The results of the evaluation using usability testing on teachers get results of 83.% and students by 87.3%. The results of the User Experience Questionnaire - Short (UEQ-S) on teachers and students got overall results, namely the Good category. It can be concluded that the solution design provides a positive perception of usability, experience, and suitability of the solution design to user problems.